2020
DOI: 10.1186/s12874-020-00932-0
|View full text |Cite
|
Sign up to set email alerts
|

The ability of different imputation methods for missing values in mental measurement questionnaires

Abstract: Background: Incomplete data are of particular important influence in mental measurement questionnaires. Most experts, however, mostly focus on clinical trials and cohort studies and generally pay less attention to this deficiency. We aim is to compare the accuracy of four common methods for handling items missing from different psychology questionnaires according to the items non-response rates. Method: All data were drawn from the previous studies including the self-acceptance scale (SAQ), the activities of d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…However, it ignored the relationship between the value of missing and other variables, which made its imputation performance was not ideal in most missing scenarios compared with other methods. This finding was consistent with the conclusion of previous research [ 26 ]. However, this study also found that under MAR (the ratio of missing proportion 1:2) mechanism, when the missing proportion was greater than about 25%, the Kappa of Mode was much higher than that of other methods.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, it ignored the relationship between the value of missing and other variables, which made its imputation performance was not ideal in most missing scenarios compared with other methods. This finding was consistent with the conclusion of previous research [ 26 ]. However, this study also found that under MAR (the ratio of missing proportion 1:2) mechanism, when the missing proportion was greater than about 25%, the Kappa of Mode was much higher than that of other methods.…”
Section: Discussionsupporting
confidence: 94%
“…Mode is one of the simplest methods to impute missing value, which is to impute missing value with the mode of not missing value of each variable [ 26 ]. It is generally used for non-numerical variables.…”
Section: Methodsmentioning
confidence: 99%
“…Digital service users reading content in online communities are more likely to be 'lurkers', individuals who will read community content but not actively participate 74 . Therefore, digital environments might be more prone to missing or misleading data around instrument completions and administration, different approaches to data imputation and how missing data is treated can have consequences in psychometric testing and measure performance 75 . Researchers in digital contexts should be aware of these issues, report missing data, and think in advance what psychometric properties the measure should be tested upon.…”
Section: Discussionmentioning
confidence: 99%
“…When the results were similar, only patients who completed the baseline, intermediate follow-up and final follow-up were included in the sensitivity analysis. This was done to avoid bias by imputation or other methods of computing missing variables [ 30 ].…”
Section: Methods and Designmentioning
confidence: 99%